Diffusion‐weighted imaging of the healthy pancreas: ADC values are age and gender dependent. Issue 4 (19th October 2012) - Herrmann, Jochen; Schoennagel, Bjoern P.; Roesch, Magdalena; Busch, Jasmin D.; Derlin, Thorsten; Doh, Laura K.; Petersen, Kay U.; Graessner, Joachim; Adam, Gerhard; Habermann, Christian R.
Abstract Purpose: To investigate the healthy pancreas with diffusion‐weighted imaging (DWI) for characterization of age and gender‐related differences in apparent diffusion coefficient (ADC) values. Materials and Methods: Sixty six volunteers were prospectively enrolled (33 male, 33 female; range 1.4 to 83.7 years of age) and echo‐planar DWI of the pancreas was performed. ADC values were measured in the pancreas head, body, and tail using a pixel‐by‐pixel approach. Effects of age and gender on ADC values were analyzed using a two‐factorial multivariate analysis of variance (MANOVA). Results: ADC values correlated inversely with the age of the volunteers. The mean global pancreatic ADC values (× 10−3 mm2/s) in the age groups 0–20 years, 21–40 years, and > 40 years were 1.18 ± 0.19, 1.07 ± 0.13, and 0.99 ± 0.18, respectively. Female individuals had higher mean global ADC values than male (1.13 ± 0.14 versus 1.02 ± 0.18 × 10−3 mm2/s). MANOVA showed significant effects of age (P value 0.022, eta2 = 0.13) and gender (P value 0.001, eta2 = 0.28) on ADC values. Conclusion: Pancreatic ADC values decline with ageing and show significant gender differences with higher mean values in females. The awareness of baseline values adjusted to age and gender will be important for correct interpretation of individual cases and design of future studies. J. Magn. Reson. Imaging 2013;37:886–891. © 2012 Wiley Periodicals, Inc.